STUDENT WORKSHEETS ON INTEGERS AND FRACTIONS BASED ON OPEN-ENDED APPROACH - Sitti Zuhaerah Thalhah; Aulia Manda; Muhammad Hajarul Aswad; Sitti Busyrah Muchsin; Mufidapuspadina (SUJANA: Education and Learning Review, 2023)
This research aims to determine the validity, practicality, and effectiveness of student worksheets in learning mathematics on integers and fractions based on open-ended approach. This type of research is Research and Development (R & D) research using the ADDIE model. Students of seventh grade of SMPN 1 Bua Ponrang were the subjects of this research. The instruments used are validation sheets for material experts, media and design experts, then practicality questionnaires for teachers and students. The data analysis technique used is descriptive qualitative and descriptive quantitative data analysis. The assessment results based on the first material expert validation questionnaire obtained a score of 78.94% which means "valid." The results of validation from the second material expert obtained a percentage score of 78.75% which is included in the "valid" category. The results of validation from media and design experts obtained a percentage score of 69.23% which means "valid." The results of practicality by educators obtained a percentage score of 98.33% with the category "very practical" and the results of practicality by students obtained a percentage score of 89.70% with the category "very practical." Based on the results of the classical provisions obtained 78.57% with an average before using the worksheet based on the open ended approach of 70.35 and after using the worksheet based on the open ended approach 76.78 which has increased in order to comply with the effectiveness category of effective. Based on these results, it can be concluded that the student worksheets based on the open-ended approach in learning mathematics on integers and fractions are valid, practical, and effective to be used as learning teaching materials.